Rachel Renee Russell Dork Diaries - Simon, Schuster (Great Britain, 2010)
New school. new crush. new mean girl. new diary, so nickki can spill all about it! Nikki Maxwell is not popular, in fact Nikki Maxwell is the opposite of popular, she's a total dork. But Nikki's hoping that by moving to a new school she might just stand a chance of making some friends and leaving her old lame ways in the past. But life is never that simple.